2022
DOI: 10.3389/fnut.2022.906409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Trends in Percutaneous Endoscopic Gastrostomy Placement: Results From a 10-Year, Nationwide Analysis

Abstract: BackgroundPercutaneous endoscopic gastrostomy (PEG) is the most commonly used access for long-term enteral nutrition. Only a few studies report the prevalence and epidemiology of PEG placements. No previous data concentrated on the healthcare system issues influencing the qualification rates and professional nutritional support for individuals with PEG.MethodsWe conducted a retrospective nationwide analysis of PEG placements in Poland from 2010 to 2020. The central data on ICD-10 coding of adult patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…We believe that this mirrors the international shift towards more minimally invasive procedures[ 17 ]. Very few studies have examined the number of gastrostomy placements in other countries, but the observed doubling of PEG is similar to the 2.5-fold increase observed in Poland from 2010-2020[ 18 ]. The United States experienced an exponential increase in PEG use from 1980-2000, resulting in more than 216000 annual PEGs[ 19 ].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We believe that this mirrors the international shift towards more minimally invasive procedures[ 17 ]. Very few studies have examined the number of gastrostomy placements in other countries, but the observed doubling of PEG is similar to the 2.5-fold increase observed in Poland from 2010-2020[ 18 ]. The United States experienced an exponential increase in PEG use from 1980-2000, resulting in more than 216000 annual PEGs[ 19 ].…”
Section: Discussionmentioning
confidence: 81%
“…In a prospectively collected case series of 1041 PEG patients in Germany, the most common indication was neurogenic dysphagia (43%), followed by cancer (37%)[ 22 ]. In the previously mentioned Polish PEG study[ 18 ], where indication was also based on ICD-10 codes, the most common indication was dysphagia and malnutrition (37.2%), which as the author states might have been a consequence of other diseases. The high proportion of non-malignant gastrointestinal conditions in this study was due to perioperative placement of a gastrostomy for stomach decompression in the case of emergency surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefits associated with PEG feeding, there is a disparity in its widespread adoption because of the risk of adverse events and lack of expertise to perform PEG. 4 , 5 , 6 This instructional video ( Video 1 ), deconstructs the steps for performing pull-type PEG.…”
mentioning
confidence: 99%